Development of a flip chart based on local wisdom regarding exclusive breastfeeding - Linda Puji Astutik; Herlinadiyaningsih Herlinadiyaningsih; Yena Wineini Migang (Institute of Computer Science (IOCS), 2023)
Exclusive breastfeeding is only given to babies from birth for 6 (six) months without adding or replacing it with food or beverages other than plain water, except vitamins, mineral drops, or medicines. The benefits provided by exclusive breastfeeding are essential for Infants and mothers; therefore, exclusive breastfeeding is a human right of infants that must be fulfilled. This study aims to describe the development of a flip chart-based media local wisdom regarding exclusive breastfeeding to improve counseling skills for midwifery students. This research uses the design of Research and Development (R & D) level 4. which seeks to make a new product in the learning system, namely the media of flip chart based on local wisdom and testing of products. Internal testing uses breastfeeding experts/practitioners, namely five breastfeeding counselors. External testing is carried out on midwifery students. The average score of counseling skills in the treatment group was found to be higher than that of the control group. The treatment group was very well motivated using a local wisdom-based flip chart higher than the control group. From qualitative data, it is stated that local wisdom-based flip charts make students happy and interested to make them more confident in providing counseling. This study concludes that the local wisdom-based flip chart media regarding exclusive breastfeeding can be used for lactation counseling media to improve lactation counseling skills.